2017
DOI: 10.1002/2016ef000479
|View full text |Cite
|
Sign up to set email alerts
|

Hypsometric control on glacier mass balance sensitivity in Alaska and northwest Canada

Abstract: Glacier hypsometry provides a first-order approach for assessing a glacier's response to climate forcings. We couple the Randolph Glacier Inventory to a suite of in situ observations and climate model output to examine potential change for the ∼27,000 glaciers in Alaska and northwest Canada through the end of the 21st century. By 2100, based on Representative Concentration Pathways (RCPs) 4.5-8.5 forcings, summer temperatures are predicted to increase between +2.1 and +4.6 ∘ C, while solid precipitation (snow)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 63 publications
0
38
1
Order By: Relevance
“…The glaciers in the GOA are anticipated to retreat significantly by the end of the century [e.g., Huss and Hock , ; McGrath et al ., ]. Given that the timing and magnitude of runoff from glacier catchments depend strongly on the areal extent of glacier ice, it is necessary to model future glacier extent prior to conducting studies to forecast hydrologic responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glaciers in the GOA are anticipated to retreat significantly by the end of the century [e.g., Huss and Hock , ; McGrath et al ., ]. Given that the timing and magnitude of runoff from glacier catchments depend strongly on the areal extent of glacier ice, it is necessary to model future glacier extent prior to conducting studies to forecast hydrologic responses.…”
Section: Methodsmentioning
confidence: 99%
“…Climate models predict that the GOA will become warmer and wetter in the future [ McAfee et al ., ], leading to significant reductions in snowpack and glacier extent [ Bliss et al ., ; Huss and Hock , ; McGrath et al ., ]. Increased precipitation and air temperature, decreased snow/rain fraction [ McAfee et al ., ], changes in land cover [ Bieniek et al ., ; McGrath et al ., ], and glacier‐derived runoff [ O'Neel et al ., ] have the potential to drive large downstream changes in the timing, magnitude, and composition of the freshwater discharge to the GOA.…”
Section: Introductionmentioning
confidence: 99%
“…Mountain glacier mass loss is ubiquitous in recent decades [ Gardner et al ., ], with some of the most rapid rates of change in Alaska [ Jacob et al ., ; Larsen et al ., ; Radić and Hock , ] and in the Arctic [ Dyurgerov et al ., ; Geck et al ., ; Nuth et al ., ; Shahgedanova et al ., ]. Glaciers in continental regions are generally losing volume at an accelerating rate [ Dyurgerov and Meier , ; McGrath et al ., ] and small mountain glaciers (~1 km 2 ) are some of the most sensitive to climate and significant contributors to total glacier coverage loss [ Bolch et al ., ; McGrath et al ., ; Paul et al ., ]. High‐latitude mountain glaciers, which represent about 50% of the world's mountain glacier area [ Björnsson et al ., ], have been identified via glacier mass balance studies to be a major source of the increased freshwater inflow to the Arctic Ocean [ Bring and Destouni , ; Dyurgerov et al ., ; Dyurgerov and Carter , ; Neal et al ., ; Weingartner et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The steady-state AAR (AAR0) was chosen to be 0.65, based on the observations of several benchmark Alaskan glaciers by Mernild et al (2013). While some studies have suggested that AAR0 values change in the future, Beamer et al (2017) found that the assumption of a steady-state AAR (i.e., keeping AAR fixed at 0.65 for the future runs) provided estimates of future glacier changes that are in accord with other published values (Huss and Hock, 2015;their figure S10;McGrath et al, 2017). As a result, we similarly assume AAR0 to be equal to 0.65 10 for the future runs.…”
Section: Future Glacier Covermentioning
confidence: 82%